Circular economy—A way forward to Sustainable Development: Identifying Conceptual Overlaps and Contingency Factors at the Microlevel. (21st October 2021) - Sinha, Ekta
Abstract: The concept of circular economy (CE) has gained a lot of attention in recent years to provide creative and innovative solutions to issues relating to sustainable development (SD) in the ever‐changing business environment. While the earlier studies have presented the concept of CE and its barriers, there exits limited work at the microlevel (business level). Additionally, most of the existing studies are case based, so generalization of results is tough. Drawing from the current literature, this work develops a deeper understanding of the concept of the CE and presents a framework of barriers at the microlevel. We identify and discuss eight major barriers to circular business (CB) processes and posit SD as the desirable outcome. The study holds some critical managerial implications as it illustrates major contingency factors and provides greater insights into CB processes for better execution.